FREQUENCY AND ASSESSMENT OF FUNGI AT DIFFERENT GRAIN FORMATION STAGES AND DISCOLORED SEEDS OF SORGHUM (SORGHUM BICOLOR (L.) MOENCH) - KOTGIRE GANESH,; S. T. PATEL, (The Bioscan, 2014)
Grain infecting fungi are important constraints for the sorghum crop grown during Kharif season particularly when grain formation stage is synchronized with high field humidity, as well as when harvesting of matured earhead is delayed. Isolation of grain-infecting fungi from earheads of field grown sorghum revealed the association of Fusarium moniliforme, Fusarium sp., Curvularia sp., Aspergillus niger, Aspergillus flavus, Alternaria alternata, Bipolaris sp., Macrophomina phaseolina, Penicillium sp. and Chaetomium sp. Frequency of the fungi on pinkish discolored, blackish discolored, brown spotted grains and smaller and shriveled grains were ranged from 2.50 to 38.75, 2.00 to 18.00, 2.75 to 18.25 and 2.00 to 14.50 per cent respectively. The loss of grain weight in different categories of grains was in the range of 27.78 to 52.28 per cent. Assessment of fungi at physiological maturity, normal maturity and two weeks after normal maturity stage of earhead revealed association of 6-9 fungi and which was ranged from 2.00 to 7.00, 3.00 to 14.00 and 2.00 to 21.00 per cent respectively.